Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran IPA Dengan Menggunakan Metode Eksperimen Di SD - ERMALINDA, ERMALINDA (Universitas Negeri Padang, 2013)
The researc start from the fart in the school that learning often dominated by teacher so students’ achievement in IPA Subject unappropriate with be hoped.King of this research in classroom action research.This research uses qualitative and quantitative research that be done with two cycle collaborately between research and the teacher.That using experiment method can improve students’achievement.From the result of study in cycle I with completeness persentage study of student is 67.9.in cycle 2 more increase than completeness persentage of study is 80,6.so it can be concluded that classroom action research using experiment method can improve students’ achievement class IV SDN 14 Tuanku Amir Kecamatan Lintau Buo Utara.